SCURTĂ ISTORIE A EDUCAȚIEI RELIGIOASE ÎN ȘCOALA PRIMARĂ ROMÂNEASCĂ A SECOLULUI XIX (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Brief History of Religious Education in the 19th Century Romanian Primary SchoolEducation in the primary schools of Romania in the 19th century was mainly a religious one. Or at least that was the way it was supposed to be. We witness the first attempts to introduce a national and compulsory system of education and its organization. The role of these schools was to teach reading, writing, and counting, together with the teaching of prayers specific to the Eastern Orthodox worship. The teacher was obliged to go to church with his students every Sunday and during the holidays and to form with them the church choir. The lack of an educational tradition, and the poverty of many villages, made these schools start quite difficult. In the beginning, the school was initially conceived to be under the shadow of the church but gradually it grew into a distinct institution. The initially dominate discipline of religion gave later way to the teaching of morality and history, but it continued to remain an important class for children for a long time. The role and importance of religion in curricula and laws of that time show that their authors implicitly believed that religious education can influence positively the development of the Romanian society, both socially and economically.